Vice-Chancellor's speech at the fourth congregation of the Midlands State University– Friday 26 August 2005 - Bhebe, Ngwabi M. (Midlands State University, 2017)
A graduation speech by Professor Ngwabi Bhebe, Vice Chancellor, Midlands State University, Zimbabwe